Contribution of Maize Polyamine and Amino Acid Metabolism Toward Resistance Against Aspergillus flavus Infection and Aflatoxin Production - Majumdar, Rajtilak; Minocha, Rakesh; Lebar, Matthew D.; Rajasekaran, Kanniah; Long, Stephanie; Carter-Wientjes, Carol; Minocha, Subhash; Cary, Jeffrey W. (Frontiers in Plant Science, 2019)
Polyamines (PAs) are ubiquitous polycations found in plants and other organisms that are essential for growth, development, and resistance against abiotic and biotic stresses. The role of PAs in plant disease resistance depends on the relative abundance of higher PAs [spermidine (Spd), spermine (Spm)] vs. the diamine putrescine (Put) and PA catabolism. With respect to the pathogen, PAs are required to achieve successful pathogenesis of the host. Maize is an important food and feed crop, which is highly susceptible to Aspergillus flavus infection. Upon infection, the fungus produces carcinogenic aflatoxins and numerous other toxic secondary metabolites that adversely affect human health and crop value worldwide. To evaluate the role of PAs in aflatoxin resistance in maize, in vitro kernel infection assays were performed using maize lines that are susceptible (SC212) or resistant (TZAR102, MI82) to aflatoxin production. Results indicated significant induction of both PA biosynthetic and catabolic genes upon A. flavus infection. As compared to the susceptible line, the resistant maize lines showed higher basal expression of PA metabolism genes in mock-inoculated kernels that increased upon fungal infection. In general, increased biosynthesis and conversion of Put to Spd and Spm along with their increased catabolism was evident in the resistant lines vs. the susceptible line SC212. There were higher concentrations of amino acids such as glutamate (Glu), glutamine (Gln) and γ-aminobutyric acid (GABA) in SC212. The resistant lines were significantly lower in fungal load and aflatoxin production as compared to the susceptible line. The data presented here demonstrate an important role of PA metabolism in the resistance of maize to A. flavus colonization and aflatoxin contamination. These results provide future direction for the manipulation of PA metabolism in susceptible maize genotypes to improve aflatoxin resistance and overall stress tolerance.